Penyuluhan Dan Pelatihan Pemanfaatan Kelapa Beserta Limbahnya Sebagai Produk Jual Untuk Meningkatkan Ekonomi Masyarakat Desa Tanjung Bunga Kecamatan Teluk Pekedai Kabupaten Kubu Raya - Gunarto Gunarto; Abdul Aziz Sulaswera (Jurnal Buletin Al-Ribaath, 2019)
The specific aim to be achieved in this activity is to motivate the public about the importance of innovation to grow the economy of the community by utilizing garden products such as coconuts to be processed food or handicraft products that can be of economic value.The expected benefits of this service for the community / stakeholders are gaining experience in exploring and growing the potential of community self-help,  obtain new ways needed to plan, formulate and implement development, the community is able to innovate and be creative to grow its economy by exploiting the potential in its environment, developing an entrepreneurship spirit in the community